Efektivitas Nematoda Entomopatogen (Steinernema spp.) Isolat Lokal Kabupaten Hulu Sungai Utara terhadap Pengendalian Ulat Grayak (Spodoptera litura F.) - Farida Adriani (Rawa Sains: Jurnal Sains STIPER Amuntai, 2012)
One type of pest damage is the armyworm (Spodoptera litura F.) which is quite significant in attacking many vegetable plants. To be able to control armyworm pests in vegetable crops, it is necessary to experiment with controlling armyworm pests using local entomopathogenic nematodes Steinernema spp. Isolates. The use of nematodes proved to be able to kill target pests. This study aims to determine the effectiveness of entomopathogenic nematodes (Steinernema spp.) local isolates of Hulu Sungai Utara Regency in the control of armyworm (Spodoptera litura F.) The study was conducted at the STIPER Amuntai Laboratory and in peanuts planting Pinangkara Village Amuntai Tengah District of Hulu Sungai Utara Regency to obtain armyworms. The study was conducted in January - March 2008. Analysis of the data used in this experiment was Annova RAL analysis followed by DMRT test if the treatment had a significant or very real effect. The results showed that the entomopathogenic nematode Steinernema spp. significantly affected the mortality of Spodoptera litura larvae. The results showed that the symptoms of Steinernema spp. Nematodes. against S. litura larvae 24 hours after application found larvae that were no longer actively involved.